2016
DOI: 10.1177/1932296816648343
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinology Telehealth Consultation Improved Glycemic Control Similar to Face-to-Face Visits in Veterans

Abstract: Background: Rates of diabetes for veterans who receive health care through the Veterans Health Administration are higher than rates in the general population. Furthermore, many veterans live in rural locations, far from Veterans Affairs (VA) hospitals, thus limiting their ability to readily seek face-to-face endocrinology care for diabetes. Telehealth (TH) technologies present an opportunity to improve access to specialty diabetes care for such patients; however, there is a lack of evidence regarding the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…A recent retrospective cohort analysis of videoconference consultation in a similar VA medical system, when used instead of the endocrine clinic visit also showed no difference in change of haemoglobin A1c between the two groups. 8 Only a few randomised clinical trials to demonstrate the efficacy of telemedicine have been carried out. [5][6][7]12,15 There is great variability in design of these studies, looking at different methods of telemedicine interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective cohort analysis of videoconference consultation in a similar VA medical system, when used instead of the endocrine clinic visit also showed no difference in change of haemoglobin A1c between the two groups. 8 Only a few randomised clinical trials to demonstrate the efficacy of telemedicine have been carried out. [5][6][7]12,15 There is great variability in design of these studies, looking at different methods of telemedicine interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in diabetic patients have shown telemedicine to be an effective strategy in improving glycaemic control [5][6][7] or non-inferior to usual clinic care. [8][9][10][11] However, only a few studies have been randomised controlled trials, [5][6][7]12 and those have randomised individual patients. Most studies used asynchronous teleconsultations or remote monitoring, where the information provided to the health-care provider and the response to patient do not occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…As for the situations in which medical teleconsultation can be indicated, this review identified 11 studies that addressed specific conditions, 7 of which used video teleconsultation and the other three used the electronic consultation system or a combination of video and telephone or even video, phone and email. Studies that compared medical teleconsultation by video with faceto-face consultations identified equivalent results regarding glycemic control of individuals with diabetes 39 , as well as in exacerbations, disease control and quality of life of patients with asthma 34 and in the treatment of childhood obesity 37 . High rates of satisfaction were also identified among patients treated for rheumatological diseases 47 and better experience of care and health outcomes in nephrology care 35 .…”
Section: Teleconsultation Indicationsmentioning
confidence: 99%
“…Multiple groups have shown positive results for diabetes care via telemedicine. Diabetes consults, provided by endocrine specialists, lead to similar hemoglobin A 1c improvement when delivered via telemedicine or traditional office visits ( 5 ). Endocrine consultation via telemedicine improves diabetes care in special populations, such as residents of correctional facilities, while helping to control costs of care related to transport ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in reimbursement structures between surgical and medical practices and across states can limit generalizability of some financial analyses. At the same time, many patients may save money from reduced travel ( 5 , 30 ) and time away from work when they access specialty care via telemedicine, and health care systems can increase their geographic reach without adding additional costly overhead expenses by using telemedicine. Telemedicine can also create more capacity for in-person visits within a practice ( 30 ).…”
Section: Introductionmentioning
confidence: 99%